The Impact of Music Training on the Cognitive Development of Preschool and Junior School Children: A Review of Research - Larisa F. Bayanova; Daria A. Bukhalenkova; Alexandra G. Dolgikh; Elena A. Chichinina (Peoples' Friendship University of Russia (RUDN University), 2021)
The review presents the results of studies of the impact of music training on the cognitive development of preschool and junior school children. It is shown that music lessons can contribute to the development of reading, writing, listening and speaking as well as mathematical skills, memory, intelligence, and executive functions. After analyzing a number of relevant studies, the authors came to the following conclusions: (1) the impact of music lessons on the development of the cognitive sphere in children is associated with concomitant factors, such as: parental involvement in music lessons and home musical environment, age when a child begins to take music lessons and their duration, socioeconomic status of the family; and 2) it is systemic music training, which includes singing, playing musical instruments and solfeggio, that can have a beneficial effect on cognitive development. The mechanisms by which music training promote the cognitive development of children were also examined. While a vast body of work confirms the beneficial effects of music training in this regard, there are a number of studies showing no such effects. Special consideration is also given to the reasons why positive research results can be erroneous. In conclusion, the authors give recommendations for designing further research on this topic as well as for organizing music lessons for children of preschool and junior school age.